A NEW ROLE OF SCHOOLS TO PROVIDE CHILD CARE SERVICES AND SUPPORT SERVICES FOR THE FAMILY - Fita Ratu Prilia; Eva Latipah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The role of the school as a child care service has made it easier for children to get care and education in preschool time and also the support services for families. This study aimed to determine the importance of the schools’ role as a child care and support services for families. The method of this study was content analysis with a research library approach. Data were collected through documentation of primary and secondary data sources. The results showed that the school readiness was a major factor that must be considered, a concept stating that children's experiences before entering kindergarten had enormous implications for development and determined their success at school. The school readiness was related to the minimum level of a child’s development to achieve the school demands through cognitive, social, and emotional qualities. Besides, tervice developers tended to involve all parties and resources into one school to seek the effectiveness and feasibility of these services. The schools should work together to build relationships between parents and educators as well as between educators within the school. Providing good quality child care was a reason to start child care services, to help schools develop and maintain good quality services.